Ответы и объяснения

Лучший Ответ!
  • Yena
  • главный мозг
2014-04-06T22:49:43+04:00
\frac{a^2+9}{a^2-9}-\frac{a}{a+3}=\frac{a^2+9}{(a-3)(a+3)}-\frac{a}{a+3}=\frac{a^2+9-a(a-3)}{(x-3)(x+3)}= \\ =\frac{a^2+9-a^2+3a}{(x-3)(x+3)}=\frac{3(3+a)}{(x-3)(x+3)}=\frac{3}{x-3} \\  \\ \frac{4ac}{a^2-c^2} \cdot \frac{a+c}{ac}=\frac{4ac}{(a-c)(a+c)} \cdot \frac{a+c}{ac}=\frac{4}{a-c} \\  \\ \frac{2x}{2x-3}-\frac{15-32x^2}{4x^2-9}=\frac{3x}{2x+3}
ОДЗ 2x-3≠0   и  2x+3≠0
         x≠1,5          x≠-1,5
2x(2x+3)-15+32x²=3x(2x-3)
4x²+6x-15+32x²=6x²-9x
30x²+15x-15=0
2x²+x-1=0
D=1+8=9
x_1=\frac{-1-3}{4}=-1 \ \ \ \ \ \ \ x_2=\frac{-1+3}{4}=0,5
спасибо, но я уже решила. все правильно)